Journal of Clinical Movement Disorders - Frucht, Steven
Journal of Clinical Movement Disorders focuses on scientific investigations into the diagnosis, evaluation and management of patients with involuntary movement disorders. The journal reviews, illustrates and emphasizes clinical phenomenology as an indispensable tool for diagnosis and application of translational medicine to movement disorders. Topics covered in the journal include Parkinson's disease, tremor, dystonia, chorea, myoclonus, Huntington's disease, tics, deep brain stimulation, botulinum toxin, and pediatric movement disorders. Journal of Clinical Movement Disorders is particularly interested in receiving submissions on international perspectives and clinical observations in movement disorders, and welcomes investigations in both hypokinetic and hyperkinetic movement disorders. Video demonstrations of patients are also strongly encouraged.